BMI increase through puberty and adolescence is associated with risk of adult stroke. (25th July 2017) - Ohlsson, Claes; Bygdell, Maria; Sondén, Arvid; Jern, Christina; Rosengren, Annika; Kindblom, Jenny M.
Abstract : Objective: To evaluate the contribution of prepubertal childhood body mass index (BMI) and BMI change through puberty and adolescence, 2 distinct developmental BMI parameters, for risk of adult stroke in men. Methods: In this population-based study in Gothenburg, Sweden, men born in 1945–1961 with information on both childhood BMI at age 8 and BMI change through puberty and adolescence (BMI at age 20–BMI at age 8) were followed until December 2013 (n = 37, 669). Information on stroke events was retrieved from high-quality national registers (918 first stroke events, 672 ischemic stroke events [IS], 207 intracerebral hemorrhage events [ICH]). Results: BMI increase through puberty and adolescence (hazard ratio [HR] 1.21 per SD increase; 95% confidence interval [CI] 1.14–1.28), but not childhood BMI, was independently associated with risk of adult stroke. Subanalyses revealed that BMI increase through puberty and adolescence was associated with both IS (HR per SD increase 1.19; 95% CI 1.11–1.28) and ICH (HR per SD increase 1.29; 95% CI 1.15–1.46). High BMI increase during puberty was strongly associated with increased risk of adult hypertension (odds ratio per SD increase 1.35; 95% CI 1.32–1.39). Conclusions: BMI increase through puberty and adolescence is associated with risk of adult IS and ICH in men. We propose that greater BMI increases during puberty contribute to increased risk of adult stroke at least partly via increased blood pressure.